Biofilm Formation Between Species Associated With Denture Stomatitis - Sharifah Nabihah Syed Abdurahman,; Nik Mohamad Faris Azzimi Nik Zulkifli,; Siti Aisyah Abd Ghafar; Syatirah Najmi Abdullah (Science Repository Journal, 2024)
Non-Indexed Publication